A decolonised Commission agenda: the missing ingredients - Kumar, R.; Arya, N. (Elsevier, 2023)
The Lancet Commission on Peaceful Societies Through Health Equity and Gender Equality1 empirically establishes that progress in health equity and gender equality could nudge societies towards peace and justice. As members of the Commission (2019–23), we withdrew from coauthorship on the principle that a decolonial lens was fundamental for the Commission's theory of change to be truly transformative. Historically, calls for decolonisation were guided by aspirations for radical dismantling of colonial structures, including the capitalist system.2 Built on legacies of imperial tropical medicine, global health is implicated in centuries of plundering, exploitation, and ongoing neocolonial extractivism.3 Today, the decolonising global health movement has compelled researchers to at least pay lip service to its demands. Recalling the work of decolonisation scholars, the Commission advocates for gender equality and health equity to be led from the inside out and cautions against imitation projects.1 Despite nodding towards self-determination, the Commission's seemingly superficial decolonial agenda resulted in three key shortcomings. The research uses a narrow approach to peace; rests its analysis on a set of health equity and gender equality indicators that are narrow in scope; and neglects the role of capitalism in current crises. Identifying structural inequalities and power asymmetries fuelled by economic and political instability, the climate crisis, and the COVID-19 pandemic, as at the root cause of multiple crises, the Commission points to failures in leadership, governance, and weakened multilateralism as contributors to escalated conflicts within societies. In testing relationships among peace, gender equality, and health equity, however, the Commission defines peace as the absence of organised violence (ie, “state-based internal armed conflict, total and civilian battle-related deaths per population resulting from varying types of conflict, and state repression”).1 Many would assert that structural violence—coined by Galtung to refer to violence inflicted by social structures and institutions—might ultimately be more destructive to human wellbeing than organised violence. As noted in the Commission report, the differential effects of the polycrisis evidence this perspective. Considering structural violence would have compelled a different set of case studies and widened the ambit of the Report's recommendations. The health equity and gender equality indicators are similarly narrow in scope. Infant mortality and life expectancy, as proxy measures for health equity, might not reflect WHO's state of complete wellbeing but seem a reasonable start. Yet, the Commission limits its analysis of health equity mechanisms to health systems, arguing that incorporating social determinants of health would require “substantial new theory development and statistical analysis”,1 despite decades-long social determinants of health work by WHO, scholars, and social movements.4,5 Given the salience of addressing structural inequalities to peace and justice, surely measures of social determinants of health should have been integrated into the analysis. Adolescent fertility and female-to-male mean years of education as proxies for gender equality, albeit accepted by the mainstream, are equally problematic. Reasons for adolescent pregnancy vary by context and might reflect the overall conditions of deprivation rather than primarily gender-based oppression. Although relevant in many settings, female-to-male mean years of education neglects the weakening of public education systems6 and decreasing academic achievement among all genders.7 A fundamental question is whether these measures universalise a hegemonic, static, culturally bound, binary, and individualistic understanding of gender.8 Indeed, the trope of teenage pregnancy is deployed by family planning programmes, favoured by donors promoting gender equality, with little attention to the broader landscape of inequality. Might appreciating the contextual nature of gender have compelled the Commission to use an indicator that at least addresses multiple dimensions of power?9 The Commission identifies “legacies of slavery and colonialism” and “geopolitics, the international political economy, the international exchange of ideas as well as efforts by multilateral organisations” as shaping health equity and gender equality,1 without naming global capitalism. Powerful private actors influence global health agenda-setting, which was prominently reflected in big pharma's role in blocking a Trade-Related Aspects of Intellectual Property Rights waiver for COVID-19 vaccine technology.10 Big tobacco, alcohol, and food have direct effects on health, while the fossil fuel and mining industries are major players in the climate crisis. Beyond wielding direct power and lobbying, these actors reinforce unhealthy narratives by influencing judicial and regulator appointments and public opinion through astroturf front groups and control of media.11 Despite their significance for health equity and gender equality, capitalism and these actors do not receive any mention in the Commission report. The way we measure problems shapes the solutions we develop. The unavailability of good quality data and potential confounders led the Commission to select a narrow set of indicators and abandon intersectional analysis. Although the absence of inequality data is itself political, the valorising of positivist approaches and large n studies deters deeper examination of complex social and political phenomena.12 Although the Commission “[believes] in the value of researchers striving for objective and generalisable research findings”,1 knowledge production, as a function of time and culture, might accentuate power asymmetries.12 Who sets the agenda in collaborative research and which types of knowledge and evidence are considered valid? The choice of Commissioners from varied cultural and disciplinary backgrounds in the Commission is laudable. However, Commissions in The Lancet are generally composed of experts either based in high-income countries, or educated at or affiliated with their elite institutions. Might neglecting structural violence, the inattention to social determinants of health, and assumptions underlying the indicators be shaped by positionality? Is the Commission's choice of issues and actors to address similarly constrained? The case studies spotlight sexual violence, particularly its community dynamics, arguably downplaying the traditional powers' role in violence, exploitation, corruption, and collective punishment.13 A previous Commission Comment,14 seemingly premised on the uniqueness of the Russian invasion in its violation of European borders and occupation, and its condemnation of the use of cluster mines, attacks on civilians, and nuclear threats might appear wilfully blind to traditional powers’ transgression and complicity15 in Yugoslavia, Palestine, or Ukraine itself. The Commission calls on decolonisation scholars to accept the importance of universal principles and their potential to guide change.1 However, a decolonial approach does not reject universalism and instead demands re-historicising and re-politicising universalist assumptions that reinforce power asymmetries and discourses that construe some peoples and places in colonial ways.8,16 A decolonial lens would have compelled the Commission to analyse structural violence, break away from epistemological power structures, and call for a radical, rather than reformist, re-envisioning of our collective futures.